An empirical study on the use of note-taking for Consecutive Interpreting in the teaching of translation - Akiko Sakamoto (JoSTrans: The Journal of Specialised Translation)
In this article, I argue that the teaching of note-taking as used in consecutive interpreting can form an effective component of the teaching of written translation, specifically for understanding the clause relations within an English text and reproducing them in a Japanese translation. The present study aims to test the validity of this claim and to discuss its implications. The study includes an account of an experiment designed to investigate whether knowledge and experience of note-taking influences students' translation products and processes. The outcome of the experiment suggests that the use of note-taking can possibly have a positive effect on the teaching of translation, especially in relation to understanding and reproducing clause relations within the text.